2022
DOI: 10.1186/s13244-021-01143-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and CT features of hepatic epithelioid haemangioendothelioma and comparison with those of liver metastases

Abstract: Background To analyse clinical characteristics and computer tomography (CT) findings of hepatic epithelioid haemangioendothelioma (HEH) and to determine differential features compared with liver metastasis (LM). Methods This retrospective study included 80 patients with histopathologically confirmed HEH (n = 20) and LM (n = 60) of different primary tumours who underwent dynamic contrast-enhanced CT scans. CT findings included the location, contour,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Due to the differences in the biological behavior of the tumor, patients with HEH had a huge discrepancy in longterm survival (16). The radiological characteristics of HEH have been reported, such as a coalescent lesion, subcapsular lesion, capsular retraction, lollipop sign, and target sign (5,17,18). We have investigated the MRI appearances of 57 patients with HEH and the results showed that capsular retraction and lollipop sign were specific features of HEH, which could be used for differential diagnosis (5).…”
Section: Discussionmentioning
confidence: 97%
“…Due to the differences in the biological behavior of the tumor, patients with HEH had a huge discrepancy in longterm survival (16). The radiological characteristics of HEH have been reported, such as a coalescent lesion, subcapsular lesion, capsular retraction, lollipop sign, and target sign (5,17,18). We have investigated the MRI appearances of 57 patients with HEH and the results showed that capsular retraction and lollipop sign were specific features of HEH, which could be used for differential diagnosis (5).…”
Section: Discussionmentioning
confidence: 97%
“…On cross-sectional imaging (CT or MRI), HEHE is often present in a subcapsular location with capsular retraction and calcifications. Enhancement can vary and present as mild homogeneous enhancement seen on all phases or thin ring-like enhancement in the arterial phase, with progressive enhancement in the portal venous phase (171) (Figure 9). The characteristic imaging sign is the “lollipop” sign, which is due to tumor spread along the portal and hepatic vein branches and sinusoids, resulting in vascular and sinusoidal narrowing and obstruction (172).…”
Section: Solid Liver Lesionsmentioning
confidence: 99%
“…The narrowing and occluded vessels are like sticks on the lesion, simulating the lollipop appearance (173). Another radiographic sign of HEHE on imaging is the “target” sign, which is an inner ring that consists of a fibrotic center, a middle ring of epithelial proliferation, and an outer ring defined by an avascular zone between the nodule and the liver parenchyma (171). The presence of capsular retraction, lollipop sign, and the target sign together is fairly specific for HEHE, and the presence of these features warrants further investigation (174).…”
Section: Solid Liver Lesionsmentioning
confidence: 99%
“…Thus, analyzing and summarizing the radiological features of HEH are very important. Several studies have reported that subcapsular lesions, coalescent lesions, capsular retraction, target sign and lollipop sign are the radiological features of HEH [ 10 13 ]. However, considering the limited cases, the results of these studies failed to provide a comprehensive description of HEH on MRI or CT scans, based on a large group of patients.…”
Section: Introductionmentioning
confidence: 99%